AUTOIMMUNE DISEASE PRESENTING AS ACUTE ABDOMEN - Memon, Wasim A.; Siddiqui, Saad; Hamza, Ameer (Journal of Ayub Medical College Abbottabad, 2017)
Mesenteric vasculitis and resultant bowel ischemia is rare but serious complication of autoimmune disorders. Early detection and treatment are the key to avoid potentially fatal outcomes of bowel perforation and peritonitis. In this series, we present patients presenting with acute abdominal pain and having CT imaging features of bowel ischemia who responded well to immunosuppressive therapy. The aim of this work is to familiarize health professionals with possibility and imaging features of mesenteric vasculitis. Keywords: Acute abdomen; Autoimmune; Laparatomy; Vasculitis; Bowel ischemia; Mesenteric vasculitis